Development of Power Supply System Solar Base for Coffee Pulper - Iqbal; Ferialdi; Paliling Agil Ricky; Azis Abdul; Mursalim; Achmad Mahmud; Waris Abdul; Hardinasinta Gemala; Mubarak Husnul; Hati Febriana Intan Permata; Rizal Muhammad (Acta Technologica Agriculturae)
Coffee pulpers generally use combustion and electric engines in operation, which have many disadvantages such as expensive fuel, pollution, and limited usage in places where electricity is supplied by the government. Therefore, a wet pulper coffee powered by an alternating current electric engine based on solar panels was developed. This study aims to produce and test a solar-powered alternating current electric engine wet pulper for coffee. This research went through several stages which are collecting secondary data, designing the tools to be developed, technical analysis, and performance test. The development of the pulper machine included an electric motor with a power of 1103.64 W, with a maximum machine rotational speed of 1400 rpm, an inverter, a 12 V and 100 A battery, a solar panel, and a 24 A solar charge controller. The performance results showed a stripping capacity of 783.176 kg∙h−1 and the best percentage of stripped coffee pulp at a machine rotational speed of 467 rpm and a mass of 3 kg. The findings show that a pulper powered by a solar-based alternating current electric engine can be a viable solution for areas without electricity and a suitable replacement for combustion engines.